2010
DOI: 10.1007/s11259-010-9443-9
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent prevalence of equid herpesvirus 5 infection

Abstract: Equid herpesvirus 5 (EHV-5) infection was detected in a farm in Italy by the use of a semi-nested polymerase chain reaction (PCR) targeting glycoprotein B of EHV-5 on nasal swabs and blood samples of clinically healthy and randomly selected Lipizzaner horses (n = 55). Twenty-five horses at the age of 4-17 years and 30 at an age of 1-3 years were sampled once. The association of the infection with these age-groups and the gender of the horses was investigated. The apparent prevalence of EHV-5 infection was sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 27 publications
2
31
0
3
Order By: Relevance
“…Equine herpesvirus‐2 has been associated with outbreaks of upper respiratory tract disease in young horses, but EHV‐2 has also been isolated from clinically normal horses . Equine herpesvirus‐5 has been associated with the development of multinodular pulmonary fibrosis (EMPF), herpetic ocular disease, and lymphoma in horses, however, these diseases are rare while of EHV‐5 shedding in the equine population is common . It has previously been reported that horses with nasal secretion viral loads of >650 000 gB genes/million cells were more likely to have EMPF than controls .…”
Section: Discussionmentioning
confidence: 48%
“…Equine herpesvirus‐2 has been associated with outbreaks of upper respiratory tract disease in young horses, but EHV‐2 has also been isolated from clinically normal horses . Equine herpesvirus‐5 has been associated with the development of multinodular pulmonary fibrosis (EMPF), herpetic ocular disease, and lymphoma in horses, however, these diseases are rare while of EHV‐5 shedding in the equine population is common . It has previously been reported that horses with nasal secretion viral loads of >650 000 gB genes/million cells were more likely to have EMPF than controls .…”
Section: Discussionmentioning
confidence: 48%
“…EHV-5 has commonly been observed in equine populations worldwide and has in general been considered a harmless virus due to its frequent detection in healthy horses (Bell et al, 2006;Marenzoni et al, 2010;Rushton et al, 2013;Torfason et al, 2008). More recently, however, it has been linked to the occurrence of equine multinodular pulmonary fibrosis (EMPF), a severe lung disease in the horse (Poth et al, 2009;Williams et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…; Marenzoni et al . ). Additionally, there is increasing evidence that EHV‐5 presents fairly large antigenic, and potentially genetic, diversity, possibly further complicating diagnosis (Ataseven et al .…”
mentioning
confidence: 97%
“…In order for EHV-5 to be identified clearly as a cause of EMPF, it is desirable that Koch's postulates be fulfilled. EHV-5 is ubiquitous and infects many horses but apparently results in EMPF in only a few (Torfason et al 2008;Fortier et al 2009Fortier et al , 2010Marenzoni et al 2010). No results of any such study have been reported at the time of writing.…”
mentioning
confidence: 99%
See 1 more Smart Citation